2007
DOI: 10.2460/ajvr.68.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of a commercial formulation of ivermectin after subcutaneous administration to sheep

Abstract: The commercial formulation of ivermectin used in this study can be administered SC to sheep on the basis of a nearly complete bioavailability. In addition, the maximum plasma concentration and interval from SC injection until maximum plasma concentration is obtained are higher than those reported by other authors who used other routes of administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
6
0
3
Order By: Relevance
“…The rapid time course of strychnine toxicity would agree with a single compartment distribution of the substance [ 32 34 ]. Ivermectin is known for its slow kinetics of distribution and excretion [ 16 ]; measurable amounts of the drug in humans and domestic animals are still found up to 17 days after administration of a single dose [ 16 , 35 , 36 ]. The ivermectin molecule is highly hydrophobic and is considered to accumulate extensively in fatty tissue which acts as a reservoir ( Figure 4(b) ), causing slow clearance from the body [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rapid time course of strychnine toxicity would agree with a single compartment distribution of the substance [ 32 34 ]. Ivermectin is known for its slow kinetics of distribution and excretion [ 16 ]; measurable amounts of the drug in humans and domestic animals are still found up to 17 days after administration of a single dose [ 16 , 35 , 36 ]. The ivermectin molecule is highly hydrophobic and is considered to accumulate extensively in fatty tissue which acts as a reservoir ( Figure 4(b) ), causing slow clearance from the body [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Durch eine systemische Bioverfügbarkeit von 50–60 % ergibt sich für diesen Stoff gemäß Biopharmaceutical Classification System (BCS) deshalb die Einordnung in die BCS-Klasse IV [ 14 , 15 ]. Durch die Anwendung von Ivermectin in gelöster Form lässt sich dessen systemische Bioverfügbarkeit deutlich erhöhen [ 16 ]. Deshalb wurde das Löslichkeitsverhalten des Arzneistoffs in relevanten Ölen untersucht, um eine Verarbeitung in gelöster Form auch gewährleisten, gleichzeitig aber auch die Quantität der Ölphase der Formulierung so gestalten zu können, dass die Stabilität der Emulsion erhalten bleibt.…”
Section: Materials Und Methodenunclassified
“…The commercially available ivermectin preparations employ different vehicles that help in stabilizing the compound. It has been reported that the bioavailability of ivermectin varies according to the nature of vehicle [28]. Lifschitz et al .…”
Section: Impact Of Ivermectin Formulations On Its Pharmacokineticsmentioning
confidence: 99%
“…In this study, oleic acid was found to be an efficient vehicle for ivermectin due to its ability to enhance the solubility and transport by reducing the p-glycoprotein (P-gp)-mediated efflux of ivermectin. The composition of various formulations of ivermectin and their characteristic features is described in Table-1 [7,26,28,32-61]. Vehicles, such as oils, liposomes, and other microparticles, can reduce drug metabolism and can enhance the release of large quantities of the active form of the drug over a long period of time to the target site by altering its pharmacokinetics [62].…”
Section: Impact Of Ivermectin Formulations On Its Pharmacokineticsmentioning
confidence: 99%